Synergistic inhibition of melanoma xenografts by Brequinar sodium and Doxorubicin - Dorasamy, Mathura Subangari; AB, Aravind; Nellore, Kavitha; Wong, Pooi Fong (Elsevier, 2019)
Malignant melanoma continues to be a fatal disease for which novel and long-term curative breakthroughs are desired. One such innovative idea would be to assess combination therapeutic treatments – by way of combining two potentially effective and very different therapy. Previously, we have shown that DHODH inhibitors, A771726 and Brequinar sodium (BQR) induced cell growth impairment in melanoma cells. Similar results were seen with DHODH RNA interference (shRNA). In the present study, we showed that combination of BQR with doxorubicin resulted in synergistic and additive cell growth inhibition in these cells. In addition, in vivo studies with this combination of drugs demonstrated an almost 90% tumor regression in nude mice bearing melanoma tumors. Cell cycle regulatory proteins, cyclin B1 and its binding partner pcdc-2 and p21 were significantly downregulated and upregulated respectively following the combined treatment. Given that we have observed synergistic effects with BQR and doxorubicin, both in vitro and in vivo, these drugs potentially represent a new combination in the targeted therapy of melanoma.